2021
DOI: 10.1002/hon.2843
|View full text |Cite
|
Sign up to set email alerts
|

Impact of comorbidities and body mass index on the outcome of polycythemia vera patients

Abstract: In 816 patients with 2016 World Health Organization‐defined polycythemia vera (PV) enrolled in a multicenter retrospective study, we investigated the predictive value of Charlson comorbidity index (CCI) and body mass index (BMI) on thrombosis, progression to post‐PV myelofibrosis (PPV‐MF) and survival. Patients were subgrouped according to CCI = 0 (58.1%, no comorbidities) or CCI ≥ 1 (41.9%) and according to normal/underweight (BMI < 25, 54.5%) or overweight/obesity (BMI ≥ 25, 45.5%) at PV diagnosis. BMI was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 37 publications
0
8
3
Order By: Relevance
“…Conventional stroke risk factors, such as hypertension and carotid atherosclerosis, were similarly distributed among patients with and without CBIs. The prevalence of arterial hypertension was ≈20% in both groups, which is lower than in several previous studies (64% in patients with PV and ET in [ 16 ]; 52.3% in PV patients in a study by Bevevolo et al [ 17 ]), which in part may be attributed to a younger age. The latter study [ 17 ] also found hypertension to be associated with increased thrombotic risk (hazard ratio (HR)—1.77 (95% CI: 1.03–3.06; p = 0.04).…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Conventional stroke risk factors, such as hypertension and carotid atherosclerosis, were similarly distributed among patients with and without CBIs. The prevalence of arterial hypertension was ≈20% in both groups, which is lower than in several previous studies (64% in patients with PV and ET in [ 16 ]; 52.3% in PV patients in a study by Bevevolo et al [ 17 ]), which in part may be attributed to a younger age. The latter study [ 17 ] also found hypertension to be associated with increased thrombotic risk (hazard ratio (HR)—1.77 (95% CI: 1.03–3.06; p = 0.04).…”
Section: Discussioncontrasting
confidence: 67%
“…The prevalence of arterial hypertension was ≈20% in both groups, which is lower than in several previous studies (64% in patients with PV and ET in [ 16 ]; 52.3% in PV patients in a study by Bevevolo et al [ 17 ]), which in part may be attributed to a younger age. The latter study [ 17 ] also found hypertension to be associated with increased thrombotic risk (hazard ratio (HR)—1.77 (95% CI: 1.03–3.06; p = 0.04). Carotid atherosclerosis was non-significantly more prevalent in patients with CBIs, and according to limited data on ET patients [ 18 ], no significant differences were found in carotid artery atherosclerosis vs. the control group.…”
Section: Discussioncontrasting
confidence: 67%
“…While age was the main factor accounting for high-risk status followed by thromboembolic complications, the vast majority of patients (> 85%) could be categorized as high risk. Unexpectedly and in contrast to published datasets (Benevolo et al 2021 ) the indication and use of pharmacologic cytoreduction was highly variable in this chart review. While at least 85% of patients had a clear indication for pharmacologic cytoreduction at the time of analysis, only 60.7% received cytoreductive medication, with a high inter-center variability (10.1–100%).…”
Section: Discussioncontrasting
confidence: 56%
“…1 A, B). This aspect is of major importance as recent studies have highlighted the impact of comorbidities on the outcome of polycythemia vera patients (Benevolo et al 2021 ). Taken together, this data indicates a patient population with a high-risk profile (more than 90% of individuals) regarding thromboembolic complications according to conventional risk stratifications.…”
Section: Resultsmentioning
confidence: 99%
“…However, whether comorbidities also affect the rate of progression in MPN patients is largely unknown. Interestingly, one study found that a higher body mass index (BMI ≥ 25) was associated with a lower probability of progression to pPV-MF and improved survival [ 59 ]. The authors speculate that normal weight or underweight may be due to a hypercatabolic state that can be associated with disease progression [ 60 ].…”
Section: Etiology Of Mpn Progressionmentioning
confidence: 99%